Re-Orienting Awareness to Human Sustainability by Integrating Indoor Spaces Strategies in Schools. Case studies from Sharjah and Ajman - ALZIR, NADIA AHMAD (2023)
A combination of global and regional methods can lead to the sustainability of the entire universe; this may also require a massive, extensive effort on a larger scale. Environmental sustainability is defined as the planet's resistance to the universe's eventual expansion- as the planet's destiny-, which is brought on by the planet's rising temperature and the greenhouse gases that will eventually produce an explosion! Fighting against this fate will slow it down, but it won't stop it! In contrast, one way to change one's perspective on "what really needs to be sustained" is to consider for whom the environment is being maintained.It's crucial to understand that sustainability includes not just environmental considerations but also social, emotional, psychological, humanitarian, and economic ones. The lack of sustainability, internally and externally, has become a significant problem in today's society. Most of the time, Sustainability is typically associated with actions taken at a global level, but it is also vital to consider its effects in our immediate surroundings, especially, in indoor environments where we spend a big portion of our lives, as well as in the most important aspect among all, Our own selves. The integration between the sustainability of indoor strategies and individual well-being are two interrelated elements that affect the overall sustainability of our environment. By choosing strategies or objectives such as Feng Shui, Biophilic design, minimalism, and Islamic principles "FBMI" -as external strategies- and then studying how they will affect occupants' neuro programming and psychological well-being - the internal section- we can create indoor spaces that do not only prioritize sustainability but also enhance the psychology and well-being of individuals..Aim: This article examines the demand for human sustainability through the educational sector by focusing on Re-Orienting Awareness to Human Sustainability by Integrating Indoor Spaces Strategies in Schools. Methodology: Two schools were selected: The International School of Creative Science in Mueileh, ISCS and Al-Shola American School in Ajman, SAS. A voice recording of two Interviews of seven questions was done with the schools' principals, plus Two types of survey questionnaires -kids and adults- were distributed on 600 responders, as follows, 400 responses from SAS and 200 responses from ISCS. Surveys targeted these categories as follows,100 kids between grades 3-6, 150 adult students between grades 7-12, and 150 teachers in SAS, meanwhile, in ISCS were distributed as 100 kids, 50 adult students and 50 teachers. The agreement scale questionnaire which targets adults and the image choice questionnaire which targets the children are the two selected types of questionnaire. Data will be analysed after collection by software such as Excel sheet ,Nvivo and SPSS. Results: An average of 74% of the 400 adult respondents agreed that the external environment variables (airflow, site orientation, natural light, greenery, minimalism, and faith) can positively impact participants' psychology; furthermore, 73.74% of the same respondents disagreed on -the participants' psychology and well-being can be healed or enhanced by the external environment variables alone-; instead, there must be internal self-healing and enhancements. Any Indoor space strategies can't be effective if the three main human components are not well sustained. > 80% of the total 400 responses from both cases, agreed that Human sustainability is required and a vital core in sustaining the environment, which is considered a high rate of DEMAND for human sustainability through schools. Reorienting our awareness towards human sustainability is a Demand.